Entrepreneurial Spirit and Entrepreneurship Education on Motivation and Interest in Entrepreneurship - Ariyanto Masnun; Poiran -; Tarjo -; Nova Elsyra; Zulkifli - (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The researchers did this related to the interest of Setih Setio Muara Bungo Institute of Administration and Health students in entrepreneurship in students of the Faculty of Administration Study Program of Business Administration and Semester VII of the State Administration Study Program, researchers indicated that there was still low interest in students in entrepreneurship as seen from their fear of loss. 175 people were used to collect library research data and field research such as interviews, observations and delivering questionnaires. The data analysis method used to test the hypothesis in this study is through SEM-PLS